Evaluation of investment strategies for rooftop distributed PV and CCS technologies in China under multiple scenarios - Yang, Changhui; Cui, Yangyu; He, Lijun; Jiang, Qi (Frontiers in Energy Research, 2022)
CCS technology is significant to achieve carbon emission reduction in the current coal-based energy mix in China, just as PV received more policy subsidies from the Chinese government to promote its industry development in the early stage, and all parties in the society, including the government and enterprises, have paid attention to and supported the development of CCS technology to promote the implementation of carbon emission reduction. This paper evaluates the regional investment benefits and investment timing of CCS retrofitting and RTDPV in different scenarios for each province in China based on the real option approach. The results show that the initial cost subsidy and participation in the carbon market are not as effective as the feed-in tariff subsidy, and the investment return of CCS retrofit is better than RTDPV in the scenario with feed-in tariff subsidy, and most provinces can achieve immediate investment. RTDPV without subsidies cannot achieve full parity nationwide yet, and some provinces are not suitable for investment without participating in the carbon market. The net present value approach would underestimate the investment value of CCS and RTDPV and prematurely reject investment in many scenarios, while provinces under the real option approach tend to delay investment to obtain optimal investment returns. This paper provides a reference for investors to make investment decisions in low-carbon technologies and for governments to develop CCS incentives.